2011
DOI: 10.1111/j.1539-6924.2011.01727.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Psychological Ripple Effects: The Role of Cultural Identity, In‐Group/Out‐Group Identification, and Attributions of Blame in Crisis Communication

Abstract: Incidents of intentional food contamination can produce ripple effects in consumers such as reduced trust and increased anxiety. In their postcrisis communication, food companies often direct the blame at the perpetrator in an effort to mitigate potential losses and regain consumer trust. The attempt to placate consumers may, in itself, potentially create psychological ripple effects in message readers. This study examined the interacting influence of two message characteristics: identity of the perpetrator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…For instance, do sit‐out strategies produce less damage in context where citizens are habituated with high levels of corruptions? These questions might move research focus about the practitioners’ perceptions of success in a crisis or about the cultural diversity of public cognitive effects and feedback on crisis situations has been focused by Anagondahalli and Turner (). Moreover, this research was also limited to only the results of the communication professionals answering the ECM survey in 2013, and hence, the results cannot be generalized as such.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, do sit‐out strategies produce less damage in context where citizens are habituated with high levels of corruptions? These questions might move research focus about the practitioners’ perceptions of success in a crisis or about the cultural diversity of public cognitive effects and feedback on crisis situations has been focused by Anagondahalli and Turner (). Moreover, this research was also limited to only the results of the communication professionals answering the ECM survey in 2013, and hence, the results cannot be generalized as such.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In fact, culture can influence perceptions and trust (Falkheimer & Heide, ). Cultural diversity of public cognitive effects and feedback on crisis situations has been focused by Anagondahalli and Turner (). They found that Asians blamed the companies more and trusted it less when a situational attribution was made in the message, while Americans did so when a personal attribution was made.…”
Section: Crisis Response Strategies Revisitedmentioning
confidence: 99%
“…Blaming can reflect the user's emotional state and efforts at mitigating potential losses. In particular, the use of negative tones in the background of communications can reveal the interlocutors' intent, as they tend to come from existing sentiments of frustration and grievance [26][27][28]. Thus, assessing the valence of messages from news reports and commentary on COVID-19 as negative or positive can help researchers reach a basic understanding of the context.…”
Section: Attributing Blame and Stigmamentioning
confidence: 99%
“…Invitational discourse implies a dynamic process where stakeholder groups continually respond to invitations to co-create narratives while, at the same time, issuing their own invitations to dialogue together. This has the effect of mitigating the potential to create in-groups and out-groups who are in defensive stand-off positions (Anagondahalli and Turner, 2012).…”
Section: Beyond Silos; Beyond Blamementioning
confidence: 99%